COOLANT CIRCULATION IMPROVEMENT ON THE CHIP TUB OF THE MACHINE LNC OKUMA 0002 PT. KOMATSU UNDERCARRIAGE INDONESIA - Prastama, Muhammad Aditya Artha; Gusniar, Iwan Nugraha; Kardiman, Kardiman (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2021)
In general, coolant is a cooling medium used to cool workpieces and cutting tools during the machining process. In PT Komatsu Undercariage Indonesia, the LNC OKUMA 0002 chip crankcase contained a lot of stagnant coolants. The factor that causes the coolant to stagnate is that the growl is wasted through the chip conveyor and the coolant is carried along with the growl to the chip. Changing the coolant fluid needs to be done in a certain phase because the use of the coolant for too long causes sand to accumulate. Excessive sand can close the cooling duct system. The quality of the coolant can deteriorate due to heat and a dirty environment. In addition, corrosion on the radiator can also result in the deposition of dirt on the coolant. When this happens, the engine overheats easily and triggers a stall. The repairs that have been carried out are examining and repairing the components of the coolant system by adding a coolant channel and a pump that functions to suck the coolant so that the coolant returns to the LNC OKUMA 0002 engine.